(untitled) (Journal of Hama University, 2025)
Introduction: Reports from the World Health Organization indicate an increase in the number of elderly people worldwide due to medical and health advancements. This number is expected to reach 1.4 billion by 2030 and 2.1 billion by 2050. With the increasing number of elderly people, significant health challenges arise, most notably chronic diseases that affect their quality of life and increase their need for continuous healthcare. In addition to prescribed medications, many elderly people resort to using herbal complementary therapy. However, using herbs without medical consultation can lead to serious interactions with pharmaceutical drugs. Aim: To assess the prevalence of herbal complementary therapy used among elderly patients and the associated factors. Materials and Methods: A descriptive analytical study was conducted after determining the appropriate sample size using the Steven K-Thompson equation. The sample consisted of 300 elderly patients collected through convenient sampling from outpatients at Tishreen University Hospital in Latakia during October 2023. Data were collected through individual interviews using a questionnaire developed by the researcher between November 15, 2023, and June 23, 2024. The data were then analyzed using the Statistical Package for the Social Sciences (SPSS V20). Results: The results showed that the prevalence of herbal complementary therapy use is 88%. Herbal therapy use is higher among males, urban residents, non-working individuals, and those with a medium level of education. It is also higher among patients without skin, heart, or glandular diseases, respectively, for a duration of 5-10 years and those who adhere to prescribed medication. Recommendations: Implement health awareness programs targeting all age groups to enhance awareness of potential drug interactions and conduct more scientific research to study the efficacy and safety of herbal therapy.